2016
DOI: 10.1007/s40789-016-0131-4
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of carbon sequestration in reclaimed coalmine degraded land dominated by Albizia lebbeck, Dalbergia sissoo and Bambusa arundinacea plantation: a case study from Jharia Coalfields, India

Abstract: Reclaimed mined lands provide an excellent opportunity to sequester carbon and combat global warming. Carbon sequestration on reclaimed sites depend on age of reclamation, composition of species, geomining conditions (soil characteristics) and prevailing climate. The aims of the present study were to calculate carbon (C)-stock of biomass of 4 years old plantation (dominated by Albizia lebbeck, Dalbergia sissoo and Bambusa arundinacea), understorey vegetation and litter, soil organic carbon in reclaimed minesoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(3 citation statements)
references
References 68 publications
1
2
0
Order By: Relevance
“…The present study analyzed the effect of afforestation of mine-degraded land using fast-growing tree species and showed a significant impact on the soil properties after eight years of afforestation. As in other studies [43][44][45], we found a positive effect of afforestation of mine soils, but we also observed different potentials of fast-growing trees to reclaim mine-degraded land. Overburden materials (mine spoil) contain a greater amount of rocks that are regraded to some extent during technical reclamation.…”
Section: Effect Of Afforestation On Mine Soilsupporting
confidence: 89%
“…The present study analyzed the effect of afforestation of mine-degraded land using fast-growing tree species and showed a significant impact on the soil properties after eight years of afforestation. As in other studies [43][44][45], we found a positive effect of afforestation of mine soils, but we also observed different potentials of fast-growing trees to reclaim mine-degraded land. Overburden materials (mine spoil) contain a greater amount of rocks that are regraded to some extent during technical reclamation.…”
Section: Effect Of Afforestation On Mine Soilsupporting
confidence: 89%
“…Moreover, the selections of exotic species are not considered to meet socio-economic requirement of the local community. In view of all such drawbacks an integrated approach was proposed which favored plantation by three-tier method [24]. The objective is to replicate natural forest with native species and biodiversity revival as existed prior to mining.…”
Section: Integrated Reclamation Approach (Three-tier Plantation)mentioning
confidence: 99%
“…The authors believe that the findings can be useful for understanding the ecosystem carbon dynamics after mining and the role of afforestation in carbon sequestration. R. Das et al [9] (2016) consider that reclaimed land (Jharia Coalfields, India) provides an excellent opportunity to sequester carbon and combat global warming. Carbon sequestration in reclamation sites depends on rock composition, geodetic conditions, soil characteristics and the prevailing climate.…”
Section: Introductionmentioning
confidence: 99%